Higher-Order Thinking Skills (HOTS)-Based Assessment in Chemistry Education: A Systematic Literature Review of Its Implementation in Senior High Schools - Manullang, Suci Setia Crise; Gea, Siska Juita Berlian Putri; Nahadi, Nahadi (Journal of The Indonesian Society of Integrated Chemistry, 2025)
Assessment based on Higher Order Thinking Skills (HOTS) plays a strategic role in chemistry learning because it encourages students to think critically, analytically, and creatively. These abilities are essential for connecting chemical concepts with real-life contexts, as well as preparing students to face the challenges of the global era and advancements in science. To formulate appropriate and evidence-based assessment strategies, an in-depth review through a Systematic Literature Review (SLR) is necessary. SLR is a method of literature review that is systematic, objective, and structured to identify trends, research gaps, and relevant empirical evidence. This review focuses on the implementation of HOTS-based assessment, particularly in the development of assessment instruments. The results show that the most commonly used instruments in HOTS-based assessment are test-based assessments, especially in the form of essay and multiple-choice questions. These findings serve as a crucial foundation for designing and developing more effective and contextual chemistry assessment practices. Keyword:    Assessment, Chemistry Learning, Higher Order Thinking Skills (HOTS)